2012
DOI: 10.1007/s00244-012-9759-2
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Perfluorooctanoic Acid (PFOA) and Perfluorooctane Sulfonate (PFOS) From Contaminated Feed Into Milk and Meat of Sheep: Pilot Study

Abstract: A pilot study was performed with dairy sheep to generate the first data on the transfer of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) from feed into food of animal origin. Corn silage was cultivated on cropland in Lower Saxony in Germany where, as a result of illegal waste disposal in 2006, farmland was contaminated with perfluorinated alkylacids (PFAAs). Two sheep were exposed by way of PFAA-contaminated corn silage to PFOS (1.16 and 1.45 μg/kg body weight [bw]/d, respectively) and PFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 36 publications
10
67
1
1
Order By: Relevance
“…For PFOS, such bioaccumulation is largely independent from the lipid content of the food item, in contrast to other POPs of food safety interest, such as chlorinated pesticides, polychlorobiphenyls (PCBs), and polychlorodibenzo-dioxins and -furans (PCDD/Fs). For sheep in a 28-d feed trial (Kowalczyk et al, 2012), at the high dose of 1450 ng kg À1 bw d À1 higher carry-over rates have been found in liver and kidney. A similar evidence was noted in the experimental trials on broilers (Yeung et al, 2009).…”
Section: Toxicokinetics and Residues In Food Of Animal Originmentioning
confidence: 98%
See 1 more Smart Citation
“…For PFOS, such bioaccumulation is largely independent from the lipid content of the food item, in contrast to other POPs of food safety interest, such as chlorinated pesticides, polychlorobiphenyls (PCBs), and polychlorodibenzo-dioxins and -furans (PCDD/Fs). For sheep in a 28-d feed trial (Kowalczyk et al, 2012), at the high dose of 1450 ng kg À1 bw d À1 higher carry-over rates have been found in liver and kidney. A similar evidence was noted in the experimental trials on broilers (Yeung et al, 2009).…”
Section: Toxicokinetics and Residues In Food Of Animal Originmentioning
confidence: 98%
“…Accounting for the modeled animal exposure (ng kg À1 bw d À1 ) via water, forages, and top soil, the correspondent concentration in edible tissues (muscle, liver, milk) was derived from animal toxicokinetics data of feeding trials with contaminated grass silage and hay reported in sheep and cow by Kowalczyk et al (2012Kowalczyk et al ( , 2013, and from the observational study in dairy cows by Vestergren et al (2013). Carry-over rates (COR), as ratio between the total amount of PFOS in the tissue/milk of the considered farmed species and the total amount ingested by the animal were derived from the sheep study for liver (9.1), and muscle (11.6).…”
Section: Carry-over Ratesmentioning
confidence: 99%
“…However, owing to the low number of data, it has not been possible to perform an assessment of the relative contribution from different foodstuffs to human exposure to PFOS and PFOA. A recent study in which contaminated feed was fed to sheep demonstrated the transfer of PFOS, PFOA and various other PFCs with different chain lengths into milk and meat of the sheep (Kowalczyk et al, 2012). As PFCs have found widespread use and ubiquitous distribution in the environment, but representative data on their occurrence in meat are still limited, an intensified monitoring of these compounds in tissues as well as feed should be considered.…”
Section: (A) Polybrominated Diphenyl Ethersmentioning
confidence: 99%
“…Perfluoroalkyl acids (PFAAs), including perfluoroalkyl carboxylic acids (PFCAs) and perfluoroalkane sulfonic acids (PFSAs) (Buck et al, 2011), are a family of perfluorinated chemicals consisting typically of a 4-14 carbon length backbone (Kowalczyk et al, 2012;Filipovic et al, 2013). Many PFAAs, which are highly resistant to degradation and are environmentally persistent (Conder et al, 2008), have been widely used in commercial and industrial products (Renner, 2001).…”
Section: Introductionmentioning
confidence: 99%